Protective Effects of Black Cumin (Nigella sativa) Oil on TNBS-Induced Experimental Colitis in Rats - AKBAY, TUĞBA (SPRINGER, 2011)
The pathogenesis and treatment of ulcerative colitis remain poorly understood. The aim of the present study is to investigate the effects of black cumin (Nigella sativa) oil on rats with colitis. Experimental colitis was induced with 1 mL trinitrobenzene sulfonic acid (TNBS) in 40% ethanol by intracolonic administration with 8-cm-long cannula under ether anesthesia to rats in colitis group and colitis + black cumin oil group. Rats in the control group were given saline at the same volume by intracolonic administration. Black cumin oil (BCO, Origo 100% natural Black Cumin Seed Oil, Turkey) was given to colitis + black cumin oil group by oral administration during 3 days, 5 min after colitis induction. Saline was given to control and colitis groups at the same volume by oral administration. At the end of the experiment, macroscopic lesions were scored and the degree of oxidant damage was evaluated by colonic total protein, sialic acid, malondialdehyde, and glutathione levels, collagen content, and tissue factor, superoxide dismutase, and myeloperoxidase activities. Tissues were also examined by histological and cytological analysis. Proinflammatory cytokines [tumor necrosis factor-alpha (TNF-alpha), interleukin (IL)-1 beta, and IL-6], lactate dehydrogenase activity, and triglyceride and cholesterol levels were analyzed in blood samples. We found that black cumin oil decreased the proinflammatory cytokines, lactate dehydrogenase, triglyceride, and cholesterol, which were increased in colitis. BCO, by preventing inflammatory status in the blood, partly protected colonic tissue against experimental ulcerative colitis.
Keywords: Colitis; Nigella sativa; Inflammation; Tissue factor activity; Oxidant damage; INFLAMMATORY-BOWEL-DISEASE; TUMOR-NECROSIS-FACTOR; ACID-INDUCED COLITIS; COLONIC INFLAMMATION; ULCERATIVE-COLITIS; TISSUE FACTOR; ANTIOXIDANT; INJURY; THYMOQUINONE; RECRUITMENT